A relationship between improved performance and job satisfaction among office support staff at RISDA in Sarawak / Alya Farah Nadya Rosli ... [et al.] - Rosli, Alya Farah Nadya; Rely, Nur Nahdatul Nadia (2016)
Chapter one consists of background of the study which explain about the variables that will be discussed for this research. It follows with the problem statement, research objectives, research questions, significance of the study, limitation and end up with the definition of the terms.